Low-Emission Alternative Energy for Transport in the EU: State of Play of Research and Innovation - Alejandro Ortega (MDPI AG, 2021)
The 2030 Climate target plan of the European Commission (EC) establishes a greenhouse gases (GHG) emissions reduction target of at least 55% by 2030, compared to 1990. It highlights that all transport modes—road, rail, aviation and waterborne—will have to contribute to this aim. A smart combination of vehicle/vessel/aircraft efficiency improvements, as well as fuel mix changes, are among the measures that can reduce GHG emissions, reducing at the same time noise pollution and improving air quality. This research provides a comprehensive analysis of recent research and innovation in low-emission alternative energy for transport (excluding hydrogen) in selected European Union (EU)-funded projects. It considers the latest developments in the field, identifying relevant researched technologies by fuel type and their development phase. The results show that liquefied natural gas (LNG) refueling stations, followed by biofuels for road transport and alternative aviation fuels, are among the researched technologies with the highest investments. Methane-based fuels (e.g., compressed natural gas (CNG), LNG) have received the greatest attention concerning the number of projects and the level of funding. By contrast, liquefied petroleum gas (LPG) only has four ongoing projects. Alcohols, esters and ethers, and synthetic paraffinic and aromatic fuels (SPF) are in between. So far, road transport has the highest use of alternative fuels in the transport sector. Despite the financial support from the EU, advances have yet to materialize, suggesting that EU transport decarbonization policies should not consider a radical or sudden change, and therefore, transition periods are critical. It is also noteworthy that there is no silver bullet solution to decarbonization and thus the right use of the various alternative fuels available will be key.